Analisa Pengaruh Kekakuan Secondary Spring Terhadap Performa Sepeda Motor Scoopy - Hidayatulloh et al., Muchammad Lutfi (Universitas Merdeka Malang, 2025)
Continuously Variable Transmission (CVT) transmission system on automatic motorcycles has an important role in efficiently distributing engine power to the wheels. One of the main components in the CVT system is the secondary spring, which plays a role in regulating the back pressure of the secondary pulley to maintain belt tension in the power transfer process, the level of secondary spring stiffness can affect the characteristics of power transfer. This study aims to analyze the effect of the stiffness of the Dytona brand secondary spring with three variations of stiffness (1000 RPM, 1500 RPM, 2000 RPM) on the performance of the Honda Scoopy motorcycle. The method used is an experiment with a quantitative approach, where each variation of the secondary spring is tested using a BRT 50 LA dyno test machine to obtain data such as power, torque, acceleration and top speed. The test results show that the secondary spring with lower stiffness provides a faster initial response and is able to maintain the transmission ratio longer at high speeds. Meanwhile, the secondary spring with higher stiffness provides a greater power boost, but reduces top speed because the transmission ratio decreases faster. It can be concluded that the selection of secondary spring stiffness must be adjusted to the desired performance characteristics, whether to achieve maximum power or optimize acceleration efficiency and high speed. This finding can be used as a reference in modifying the CVT system to improve motorcycle performance, especially the Honda Scoopy